The son of the wolf - London, Jack, 1876-1916 (Floating Press, 2010)
Love Jack London's classic adventure novel The Call of the Wild? Curl up with this collection of short stories in the same vein. The tales in The Son of the Wolf, most of which are set in the Klondike region of the Yukon, highlight London at his very best.